When the Gospel meets the China Dream: Religious Freedom and the Golden Rule - Chiaretto Yan, Kin Sheung (International Bulletin of Mission Research, 2018)
The issue of religious freedom affects Sino-Vatican relations, but the Roman Catholic Church shares values with Confucianism, which provides common ground for dialogue. Pope Francis is focusing the church outward by promoting a culture of encounter and by working unceasingly for a fraternal dialogue of peace. Chinese president Xi Jinping urges his people to fulfill the China dream, emphasizing the core values of harmony, friendship, and civilization. Many have believed that the Gospel can contribute to China?s spiritual civilization; normalization of relations between China and the Holy See would benefit China and the Catholic Church and contribute to world peace and harmony.
Publisher: SAGE Publications Ltd

A Confucian Perspective on Tertiary Education for the Common Good - Eh, Edmond (The Journal of the Macau Ricci Institute, 2018)
Confucian education is best captured by the programme described in the Great Learning. Education is presented first as the process of self-cultivation for the sake of developing virtuous character. Self-cultivation then ...
GSCC: 0000010

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

Book Review: ‘The Catholic Invasion of China: Remaking Chinese Christianity’, by D. E. Mungello (Lanham, MD: Rowman & Littlefield, 2015) - Law, Cyril Jerome (Heythrop Journal, 2018)

Newman and the Ministerial Priesthood - Law, Cyril Jerome (Friends of the Ordinariate, 2018)

Creating multiculturalism amidst ethnic, linguistic and religious diversity: a Filipino perspective. - Monera, Arnold (Multiculturalism in Asia – Peace and Harmony, 2018)

What Kinds of Comparison Are Most Useful in the Study of World Philosophies? - Sivin, Nathan; Akasoy, Anna; Anderson, Warwick; Colas, Gérard; Eh, Edmond (Journal of World Philosophies, 2018)
GSCC: 0001339 Number: 2
Keywords: comparative history; connected history; cultural manifolds; diachronic; intellectual history; inter-cultural comparison; intra-cultural comparison; mutual pollination; postcolonial history; synchronic; transnational history